Monitoring and Comparison of Antibiotic Resistant Bacteria and Their Resistance Genes in Municipal and Hospital Wastewaters - Aali, Rahim (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Human exposure to antibiotic resistant bacteria (ARB) is a public health concern which could occur in a number of ways. Wastewaters seem to play an important role in the dissemination of bacteria and antibiotic resistant genes (ARGs) in our environment. The aim of this study was to evaluate the occurrence of three groups of ARB and their resistance genes in hospital and municipal wastewaters (MWs) as possible sources. METHODS: A total of 66 samples were collected from raw MWs and hospital wastewaters (HWs) and final effluents of related wastewater treatment plants (WWTPs). Samples were analyzed for the detection of three groups of ARB including gentamicin (GM), chloramphenicol (CHL) and ceftazidime resistant bacteria and their ARGs (aac (3)-1, cmlA1 and ctx-m-32, respectively). RESULTS: The mean concentration of GM, CHL and ceftazidime resistant bacteria in raw wastewater samples was 1.24 × 10(7), 3.29 × 10(7) and 5.54 × 10(7) colony forming unit/100 ml, respectively. There is a variation in prevalence of different groups of ARB in MWs and HWs. All WWTPs decreased the concentration of ARB. However, high concentration of ARB was found in the final effluent of WWTPs. Similar to ARB, different groups of ARGs were found frequently in both MWs and HWs. All genes also detected with a relative high frequency in effluent samples of MWs WWTPs. CONCLUSIONS: Discharge of final effluent from conventional WWTPs is a potential route for dissemination of ARB and ARGs into the natural environment and poses a hazard to environmental and public health.